PATTERN OF ANTIBIOTICS UTILIZATION IN NEONATAL SEPTICEMIA: A CROSS-SECTIONAL STUDY FROM RURAL TERTIARY CARE HOSPITAL WESTERN MAHARASHTRA, INDIA - R., Shinde A.; V., Mohite R.; V., Shinde R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To assess the quantification of use of antibiotics and to find out empiric antibiotic regimen practiced for neonatal sepsis in rural tertiary health care centre. Methods: A hospital, record based cross-sectional study was conducted in Neonatal Intensive Care Unit(NICU) at tertiary care hospital located in western Maharashtra, India. The study was planned during the year 2011-12 among 84 neonates with sepsis. Data were collected by using proforma includes demographic details, antibiotic prescriptions and relevant information. Results: Among the total 84 neonates, max, 60.71% had a history of term delivery. The proportion of early and late onset of sepsis was 47.61% and 52.38% for which total 18 antibiotics were used of which max, 88.88% were injectables. Amikacin was used in max, 78.57% neonates followed by cefotaxime, 45.23% and ampicillin, 35.71% in single or combination form respectively. Amikacin was used for max; 929 d followed by cefotaxime, 523 d and ampicillin 331 d respectively. Antibiotics used in single, double and multiple regimens were 19.04%, 46.42% and 34.52% respectively. Empiric antibiotic regimens practiced were cefotaxim+amikacin and cefotaxim+ampicillin, of which max, 80% patients were treated with the cefotaxim+amikacin antibiotic regimen. Out of 84 neonates max, 70% were improved at the time of discharge. Conclusion: Neonatal sepsis was well treated by cefotaxim+amikacin empirical injectable regimen with maximum survival.